Analisis kadar kolesterol total terhadap peningkatan tekanan darah - Annisa, Istiana; Prihati, Manis; Armal, Hadist Lissentiya; Brigita, Marlin L. (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Cholesterol is a type of lipid metabolite containing sterol compounds that is highly concentrated in cell membranes and within the circulatory system. An increase in blood cholesterol levels, known as hypercholesterolemia, initiates the accumulation of body fat, which in turn contributes to a rise in blood pressure. This condition plays a significant role in the development of hypertension. Purpose: To determine the distribution of respondents according to their cholesterol levels and blood pressure, as well as to identify whether there is a significant relationship between cholesterol levels and blood pressure. Method: This study was cross-sectional with a descriptive quantitative approach. The independent variable was blood pressure and the dependent variable was total cholesterol level, with the sample selected using a purposive sampling technique. Results: The statistical test yielded a P-value of 0.001 (P-Value <0.05), indicating a significant relationship between total cholesterol levels and blood pressure. The odds ratio (OR) for both variables was 6.585. Total cholesterol levels were 6.6 times more likely to influence respondents' blood pressure. Conclusion: There is a significant relationship between total cholesterol levels and blood pressure. Keywords: Cholesterol; Hypertension. Pendahuluan: Kolesterol merupakan lemak hasil metabolit yang mengandung senyawa sterol dan banyak terkonsentrasi pada membran sel di dalam tubuh serta sistem sirkulasi. Peningkatan kadar kolesterol dalam darah (hiperkolesterolemia) mengawali terjadinya lonjakan lemak tubuh yang pada akhirnya menyebabkan peningkatan tekanan darah. Tujuan: Mengetahui distribusi responden berdasarkan kadar kolesterol total, dan tekanan darah, serta mengetahui hubungan yang bermakna antara kadar kolesterol total dengan tekanan darah. Metode: Penelitian ini bersifat cross sectional dengan pendekatan kuantitatif deskriptif. Variabel independen adalah tekanan darah dan variabel dependen adalah kadar kolesterol total dengan pemilihan sampel menggunakan teknik purposive sampling. Hasil: Uji statistik diperoleh nilai P = 0.001 (P-Value < 0.05), sehingga dapat dinyatakan ada hubungan yang bermakna antara kadar kolesterol total dengan tekanan darah. Kedua variabel tersebut diperoleh nilai odds ratio (OR) sebesar 6,585. Kadar kolesterol total memiliki kemungkinan 6.6 kali lebih besar untuk berpengaruh terhadap tekanan darah responden. Simpulan: Ada hubungan yang bermakna antara kadar kolesterol total dengan tekanan darah Kata Kunci : Hipertensi, Kolesterol